Relationship between cholesterol levels and anxiety levels among hypertension patient in the community setting - Amanda, Lavenia Megy; Sholihin, Sholihin; Toga, Erik (The Journal of Palembang Nursing Studies, 2023)
Background: Cholesterol is needed by humans for glucose metabolism and it also plays an important role in human energy metabolism. However, having too much cholesterol can also harm the individual himself, which can lead to the accumulation of fat in the blood. Objective: The purpose of this study was to determine the relationship between cholesterol levels and anxiety levels on hypertension in the working area of Klatak Health Center. Methods: The research design used a Correlation Study with a cross-Sectional research design. The study population was 70 respondents with hypertension and as many as 60 respondents were selected by using a purposive sampling technique. The research instrument used a cholesterol meter and an Anxiety Questionnaire Hamilton Rating Scale for Anxiety (HRS-A). Data analysis in this study used the Spearman Rank. Results: The result of cholesterol levels with anxiety levels in patients with hypertension (p = 0.003; r = 0.380) which mean that there was a relationship between cholesterol levels and anxiety levels in the working area of Klatak Health Center. Conclusions: The conclusion is that with better cholesterol levels in patients with hypertension then the level of anxiety in diseases will be reduced.